THE EFFECT OF TEAMS GAMES TOURNAMENT (TGT) MODIFIED SCHEMA BASED INSTRUCTION (SBI) ON MATHEMATICS PROBLEM SOLVING ABILITY OF GRADE V STUDENTS [PENGARUH TEAMS GAMES TOURNAMENT (TGT) MODIFIKASI SCHEMA BASED INSTRUCTION (SBI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V] - Monica Abolla; Yurniwati (Universitas Pelita Harapan, 2026)
Mathematical problem-solving skills are important to develop in learning mathematics in elementary schools. However, the fact that occurs is that students' ability in this competency is still lacking. This study aims to determine whether there is a difference in the mathematical problem-solving ability of students who learn using the Teams Games Tournament method modified by Schema-Based Instruction with students who learn using the expository method. This study used experimental research methods on fifth grade students of SDN Beumopu and was conducted from January to June 2025. The sampling technique used was cluster random sampling. The samples in the experimental class and control class amounted to 32 students each. Data collection utilized mathematical problem-solving ability test instruments in the form of essay questions. Indicators of mathematical problem-solving ability include understanding the problem, planning problem-solving strategies, and implementing problem-solving plans. The results showed that the problem-solving ability of fifth-grade students who learned with the SBI modified TGT method was higher than that of students who learned with the expository method. Abstrak Bahasa Indonesia Kemampuan pemecahan masalah matematika penting untuk dikembangkan pada pembelajaran matematika di sekolah dasar. Namun, fakta yang terjadi adalah kemampuan siswa pada kemampuan pemecahan masalah siswa masih kurang. Penelitian ini bertujuan untuk mengetahui adakah perbedaan kemampuan pemecahan masalah matematika siswa yang belajar menggunakan metode Teams Games Tournament modifikasi Schema Based Instruction dengan siswa yang belajar menggunakan metode ekspositori. Penelitian ini menggunakan metode penelitian eksperimen pada siswa kelas V SDN Beumopu dan dilaksanakan dari bulan Januari sampai bulan Juni 2025. Teknik pengambilan sampel menggunakan cluster random sampling. Sampel pada kelas eksperimen dan kelas kontrol masing-masing berjumlah 32 siswa. Pengumpulan data menggunakan instrumen tes kemampuan pemecahan masalah matematika berupa soal esai. Indikator kemampuan pemecahan masalah matematika adalah memahami masalah, merencanakan strategi penyelesaian masalah dan melaksanakan rencana penyelesaian masalah. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah siswa kelas V yang belajar dengan metode TGT modifikasi SBI lebih tinggi dibandingkan dengan siswa yang belajar dengan metode ekspositori.